Reluctant revolutionaries : New York City and the road to independence, 1763-1776 - Tiedemann, Joseph S. (Cornell University Press, 1997)
The question of why New Yorkers were such reluctant revolutionaries has long bedeviled historians. In an innovative study of New York City between 1763 and 1776, Joseph S. Tiedemann explains how conscientiously residents labored to build a consensus under difficult circumstances. New Yorkers acted the way they did not because they were mostly loyalist or because a few patrician conservatives were able to stem the tide of revolution but because the population of their city was so heterogeneous that consensus was not easily achieved.